1993
DOI: 10.1200/jco.1993.11.6.1132
|View full text |Cite
|
Sign up to set email alerts
|

High-dose chemotherapy and autologous bone marrow support as consolidation after standard-dose adjuvant therapy for high-risk primary breast cancer.

Abstract: High-dose consolidation with CPA/cDDP/BCNU and ABMS after standard-dose CAF results in a decreased frequency of relapse in patients with high-risk primary breast cancer compared with historical series at the median follow-up of 2.5 years. Evaluation in a prospective, randomized trial is warranted and currently underway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
179
2
6

Year Published

1993
1993
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(191 citation statements)
references
References 17 publications
4
179
2
6
Order By: Relevance
“…We believe that the first category, the STAMP-I regimen, is too toxic for routine use. The two studies (Peters et al, 1993;Nikcevich et al, 2002) that employed this carmustine-based combination reported high toxic death rates due to organ toxicity, mainly interstitial pneumonitis. Even very experienced centres that optimally exploit corticosteroids at the earliest sign of pulmonary symptoms report a 5% toxic death rate (Antman et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the first category, the STAMP-I regimen, is too toxic for routine use. The two studies (Peters et al, 1993;Nikcevich et al, 2002) that employed this carmustine-based combination reported high toxic death rates due to organ toxicity, mainly interstitial pneumonitis. Even very experienced centres that optimally exploit corticosteroids at the earliest sign of pulmonary symptoms report a 5% toxic death rate (Antman et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…At Duke University, in a phase II study Peters et al 22 reduced duration of aplasia and hospitalization. 35 However, much of the therapy-related mortality observed is due to used high-dose cyclophosphamide, cisplatinum and carmustine with autologous stem cell support as consolidation the organ toxicity due to the conditioning regimen and is independent of the source of hematopoietic support.…”
Section: Treatment Programmentioning
confidence: 99%
“…Breast cancer patients with four or more positive axillary lymph nodes have historically had a poor prognosis (Jatoi et al, 1999), even with conventional adjuvant chemotherapy (EBCTCG, 2005). A series of uncontrolled studies of high-dose chemotherapy in the 1990s, mainly using an induction/intensification strategy, in which patients received conventional chemotherapy followed by highdose chemotherapy as a late intensification regimen, produced results that showed a substantial benefit for high-dose regimens (Antman et al, 1992;Peters et al, 1993). High-dose therapy soon became a widely used treatment option for women with bad-risk breast cancer, even without supporting evidence from randomised controlled trials.…”
mentioning
confidence: 99%